Risk mitigation study for hydrogen releases from hydrogen fuel cell vehicles - Han, Hyejeong; Kim, Shinji; Park, Junyong; Kim, Gyuwon; Jung, Seungho (International Journal of Hydrogen Energy, 2024)
There has been an increase in environmental degradation associated with the use of fossil fuels in an attempt to meet the ever-increasing demand for electricity. Therefore, alterative renewable energy sources have garnered the attention of many researchers globally; hydrogen is an important example due to its eco-friendly nature. For hydrogen to be used as an energy source, it has to first be compressed. The explosion of high-pressure hydrogen vessels has been the driver of most accidents associated with its use. To prevent explosions, thermally activated pressure relief devices (TPRDs) are used to release hydrogen. The TPRD release orientations in a tunnel, which is a confined space, were investigated in this study based on a high-pressure release of hydrogen. In addition, we also propose an evacuation and safety protocol in the event of such an accident. In addition, the dynamics associated with the release of hydrogen were analyzed based on vehicle type. We found that in passenger cars and buses, hydrogen is released from the bottom and top, respectively. The dispersion range in this study was simulated based on a hydrogen concentration of 4%, in which air currents, including those from jet fans in the tunnel, are considered. The results confirm that passenger cars are barely affected by the jet fan airflow, and backward release facilitates evacuation and secures a safety zone more effectively compared with vertical emission. Meanwhile, upward releases were significantly affected by the jet fan. Overall, release in the airflow direction, regardless of the tunnel location, was confirmed to be effective in the context of evacuation and securing safety zones for buses.
Keywords: Emergency response; Hydrogen fuel cell vehicles; Hydrogen release; Hydrogen safety; Jet fans; Pressure relief devices; Risk mitigation; Safety zone; Thermally activated; Thermally activated pressure relief device; Computational fluid dynamics; Emergency response; Hydrogen safety; Thermally activated pressure relief device; Tunnel